Researches on feeding behaviors of Nezara viridula (Linnaeus, 1758)(Hemiptera: Pentatomidae) adults in intermittent CO2 applications - Özgen, İnanç; Birgücü, Ali Kemal; Aydoğmuş, Ercan; Güral, Yunus; Topdemır, Aykut (My University, 2024)
In this study, the effects of 3 different doses (430, 600 and 670 ppm) of intermittent CO2 applications on the feeding behaviors of Nezara viridula L. (Hemiptera: Pentatomidae) Adults were determined. As nutritional behavior, the total nutrition duration of adult male and female individuals other than nutrients was examined. As a result of the study, no statistically significant difference was found between the total feeding times of female and male individuals of N. viridula. A statistically significant difference was found between the duration of stay on the nutrients of female and male individuals of N. viridula who received 600 ppm and 670 ppm doses of CO2. The duration of stay on the nutrients of male individuals who received 600 ppm and 670 ppm doses of CO2 was found to be significantly lower than the duration of stay on the nutrients of female individuals. The duration of stay on the nutrients of male individuals who received 670 ppm doses of CO2 was found to be significantly lower than the duration of stay on the nutrients of female individuals. No statistically significant difference was found between the CO2 dose groups of N. viridula and the total feeding times of the control group. A statistically significant difference was found between the CO2 dose groups of N. viridula and the duration of stay apart from the nutrients and the duration of stay on the nutrients of the control group. The duration of stay on the nutrients of individuals exposed to 600 and 670 ppm CO2 doses was found to be significantly lower than the duration of stay on the nutrients of individuals in the control group. In addition, the duration of stay apart from the nutrients of the individuals to whom 600 and 670 ppm CO2 doses were applied was found to be significantly higher than the duration of stay apart from the nutrients of the individuals in the control group. As a general result of this study, it was determined that as the application dose increased, the feeding behaviors of male and female individuals changed, male individuals reacted more to dose administration and remained on nutrients less than female individuals.
Keywords: Nezara viridula; Feeding Behaviors; Intermittent CO2